ANALISIS PENGARUH MODAL KERJA TERHADAP PROFITABITAS (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017 - 2019) - Achmad Otarianto (Prospect : Jurnal Manajemen dan Akuntansi, 2023)
This study aims to determine the effect of working capital on the profitability of textile and garment manufacturing companies listed on the Indonesia Stock Exchange 2017-2019. The sample selection method used purposive sampling. This study uses multiple regression analysis methods, coefficient of determination, multiple correlation analysis, and hypothesis testing (F test and T test) to test the effect of independent variables on the dependent variable. The independent variables used to measure working capital are cash turnover, accounts receivable turnover, and inventory turnover. And the dependent variable used to measure profitability is Return On Assets (ROA). The number of research samples is as many as 6 textile and garment companies listed on the Indonesia Stock Exchange 2017-2019. The results of this study indicate that the variables of cash turnover, accounts receivable turnover, and inventory turnover have a significant effect on ROA.Keywords: Working Capital, Cash Turnover, Accounts Receivable Turnover, Inventory Turnover and ROA